Multipass inkjet printed planar methylammonium lead iodide perovskite solar cells. Issue 48 (29th November 2016) - Mathies, Florian; Abzieher, Tobias; Hochstuhl, Adam; Glaser, Konstantin; Colsmann, Alexander; Paetzold, Ulrich W.; Hernandez-Sosa, Gerardo; Lemmer, Uli; Quintilla, Aina
Abstract : Multipass inkjet printing and vacuum drying of MAPbI3 perovskite for better film thickness and crystal size control. Abstract : We report the fabrication and optimization of multipass inkjet-printed perovskite solar cells. The presented process allows excellent control of crystallization dynamics and thickness of the perovskite layer. In order to obtain a homogenous perovskite film of large and densely packed crystals on a planar TiO2 electron transport layer we make use of an additional vacuum annealing step. Its beneficial impact was characterized in terms of device performance and laser beam induced current mapping as well as atomic force microscopy. The optimized fabrication methods resulted in power conversion efficiencies up to 11.3% of multipass inkjet printed perovskite solar cells. The spin coated reference devices reached 12.8% power conversion efficiency. With these first results, we advance the field of digital printing techniques for perovskites and demonstrate a major step towards highly efficient, low-cost and less Pb-waste producing perovskite solar cells.